Combination of Compost and Mineral Fertilizers as an Option for Enhancing Maize (Zea mays L.) Yields and Mitigating Greenhouse Gas Emissions from a Nitisol in Ethiopia - Gebeyanesh Worku Zerssa (MDPI AG, 2021)
Combined application of organic and mineral fertilizers has been proposed as a measure for sustainable yield intensification and mitigation of greenhouse gas (GHG) emissions. However, fertilizer effects strongly depend on the soil type and still no precise information is available for Nitisols in Ethiopia. The study evaluated effects of different ratios of biowaste compost and mineral fertilizers (consisting of nitrogen (N), phosphorus (P), and sulphur (S)) on maize (Zea mays L. Bako-hybrid) yields in a two-year field trial. Soil samples from each treatment of the field trial were used to estimate emissions of nitrous oxide (N2O), carbon dioxide (CO2), methane (CH4), and microbial activity in a 28-day incubation experiment with two moisture levels (40% and 75% water-filled pore space, WFPS). The application of fertilizers corresponded to a N supply of about 100 kg ha−1, whereby the pure application of mineral fertilizers (100 min) was gradually replaced by compost. Maize yields were increased by 12 to 18% (p < 0.05) in the combined treatments of compost and mineral fertilizers compared to the 100 min treatment. The cumulative emissions of N2O and CO2 but not CH4 were affected by the fertilizer treatments and soil moisture levels (p < 0.05). At 75% WFPS, the N2O emissions in the 100 min treatment was with 16.3 g ha−1 more than twice as high as the treatment with 100% compost (6.4 g ha−1) and also considerably higher than in the 50% compost treatment (9.4 g ha−1). The results suggest that a compost application accounting for 40 to 70% of the N supply in the fertilizer combinations can be suitable to increase maize yields as well as to mitigate GHG emissions from Nitisols in Southwestern Ethiopia.